The charismatic renewal in Malacca: A sociological study / Rebecca Yeo Guat Lin - Rebecca, Yeo Guat Lin (1983)
Chapter I is an introduction to the aims and purpose, the methods used and the problem faced in conducting this research. Chapter II deals with the emergence of the charismatic renewal in the world and in Malaysia. Certain important concepts of this study are defined here. The origin of the movement and its penetration and spread into the Malaysian society especially into the established churches are also discussed. Chapter III introduces the groups under study. A general idea of the forms of worship and activities participated by the followers of the charismatic movement are shown here. Chapter IV is an investigation of the backgrounds and recruitment of the leaders and members of the various Charismatic groups in Malacca. The aim of this chapter is to give the reader an understanding of the types of people who are attracted to such movements. Chapter V gives some insights into the workings of the charismatic groups in Malaccca, such as the formation of the groups, the organizational structure, the financial situation, conflict and solidarity between the groups, links and affiliation between the groups and churches and the role of the priests in the charismatic renewal. The conclusion offers plausible explanations of the growing popularity and the spread of the charismatic renewal movement in Malaysia. This is the main aim of the study.